Ultrafast excitation quenching by the oxidized photosystem II reaction center - Akhtar, Parveen (2022)
Photosystem II (PSII) is the pigment-protein complex driving the photoinduced oxidation of water and reduction of plastoquinone in all oxygenic photosynthetic organisms. Excitations in the antenna chlorophylls are photochemically trapped in the reaction center (RC) producing the chlorophyll-pheophytin radical ion pair P+ Pheo-. When electron donation from water is inhibited, the oxidized RC chlorophyll P+ acts as an excitation quencher, but knowledge on the kinetics of quenching is limited. Here, we used femtosecond transient absorption spectroscopy to compare the excitation dynamics of PSII with neutral and oxidized RC (P+). We find that equilibration in the core antenna has a major lifetime of about 300 fs, irrespective of the RC redox state. Two-dimensional electronic spectroscopy revealed additional slower energy equilibration occurring on timescales of 3-5 ps, concurrent with excitation trapping. The kinetics of PSII with open RC can be described well with previously proposed models according to which the radical pair P+ Pheo- is populated with a main lifetime of about 40 ps, which is primarily determined by energy transfer between the core antenna and the RC chlorophylls. Yet, in PSII with oxidized RC (P+), fast excitation quenching was observed with decay lifetimes as short as 3 ps and an average decay lifetime of about 90 ps, which is shorter than the excited-state lifetime of PSII with open RC. The underlying mechanism of this extremely fast quenching prompts further investigation.